FUSI CITRA LANDSAT 7 ETM+ DAN CITRA ASTER G-DEM UNTUK IDENTIFIKASI ZONA ALTERASI HYDROTHERMAL TERKAIT MINERAL DI SEBAGIAN KALIMANTAN BARAT - , IRVAN NURRAHMAN A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia as an archipelagic country, has a huge potential of mineral resources. This because Indonesia is a country surrounded by old and young volcanoes. West borneo, geologically is an old volcanic areas may indicate hydrothermal alteration rocks. Hydrothermal alteration rocks can be use for indicator of a variety of minerals. LANDSAT 7 ETM + imagery and ASTER G-DEM imagery as remote sensed data with a variety of image processing techniques such as Principal Component (PC) fusion, Intensity, Hue, and Saturation (IHS) fusion, image fusion from Band Ratioing method and spatial filtering needs to be compared to know the best image processing. In addition, the physical aspects of terrain such as landforms, rocks (lithology), and geological structure analysis also needs to be done related t identification of hydrothermal alteration zones. This study aimed to determine the ability of some image processing techniques in identification of hydrothermal alteration zones and mapping hydrothermal alteration zones associated with landforms, rocks (lithology), and structural geology. Physical aspects of terrain parameters obtained through visual interpretation of landforms, rock (lithology), and geological structures assisted with image processing techniques. In addition a laboratory analysis like petrographic analysis was conducted to find the mineral content of the rocks for determination of hydrothermal alteration zones. Results of the analysis showed Principal Component (PC) fusion techniques has the highest accuracy of landform with 71.15%. Highest accuracy for rocks (lithology) is 70.98% from Intensity, Hue, and Saturation fusion techniques. Mapping of hydrothermal alteration zones shows 4 hydrothermal alterated zones, there are Argilic alteration zone with an area of 1399,42 km 2 , 2913,46 km 2 zone of potassic alteration, Propilitic alteration zone 1160,54 km 2 , and 946,38 km 2 zone of Serisitic alteration.